Hubungan Tingkat Spiritual dengan Kejadian Quarter Life Crisis pada Mahasiswa Tingkat Akhir - Naimi Syifa Urrahma; Sri Wahyuni; Wasisto Utomo (Jurnal Kesehatan Komunitas, 2022)
Introduction: Quarter-life crisis is a phenomenon that occurs in their 20s. Spirituality is referred to as one of the factors associated with the quarter-life crisis. The purpose of the study was to determine the relationship between individual spiritual levels and the incidence of quarter-life crises in final-year students. Methods: The research design used was a descriptive correlation with a cross-sectional. This research was conducted at a university in Riau on 224 final-year students from ten faculties using a proportional random sampling technique. The measuring instrument used is the Spiritual Well-Being Questionnaire (SWBQ) and Quarter life crisis with validity values ​​(of 0.466-0.757) and (0.496-0.858). Simple descriptive tests and chi-square were used in data analysis. Research Results: The spiritual level of students is at a low level of 31 students (13.8%), a medium level of 148 students (66.1%), and a high level of 45 students (20.1%). The spiritual dimension of the personal part is the lowest part among other dimensions students 86.2 %). Statistical test results obtained a p-value (0.000) < (0.05), which means that there is a significant relationship between spiritual level and the incidence of quarter-life crisis in final-year students. Conclusion: Spirituality is important for students in an effort to prevent a quarter-life crisis. An effort is needed to improve the spirituality of final-year students, especially on the personal side to prevent the occurrence of a quarter-life crisis.